Stakeholders’ Perspectives on Border Region Development: West Southeast Maluku, Indonesia - Nuzula Anggeraini; Yeremias T. Keban; Jun Matsunami (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2018)
Border regions are geographically presented with potential economic benefits. However, some of these areas have not been able to take advantage of their strategic geographic locality. This is also the case for border areas in Indonesia. There is a spectrum of perceptions by stakeholders on how border regions, particularly international borders, should be developed. This study sought to capture the perspectives of Indonesian stakeholders on border region development, and the extent of influence such perspectives have in the policy of border areas development with a case study in West Southeast Maluku The research was conducted using qualitative method with in-depth interviews as the primary collecting data technique. The results show that despite perceptions of stakeholders who view West Southeast Maluku as an area of insecurity, they also see the potential of the area to be developed as a gateway, area of opportunity, zone of contacts and zone of cooperation. However, the current policies and strategies of the development of border areas do not exemplify such perceptions, and the formulation of such policies is likely to be dominated by state-level stakeholders, despite the fact that local level stakeholders have a more comprehensive understanding of the needs of their areas.